Symbolika namaszczenia głowy i obmycia twarzy przez poszczącego (Mt 6, 17) w interpretacji patrystycznej - Nieścior, Leon (Vox Patrum, 2020)
In ancient commentators we find some reflection on the recommendation to anoint faces and to wash one’s head during fasting (Matthew 6:17). By adhering to the essence of this message, and thus the evangelical call to humbleness and lack of ostentation in fasting, the Fathers consider the necessity of public fasting in some specific cases. Cassiodorus links fasting for show with the attitude of the foolish virgins (Matthew 25:1–13), who had no oil for their lamps, meaning they had no attention for the Lord because they did their good deeds only to flatter others. To our authors, face washing in Matthew6:17 stands for honesty of conscience, and above all, moral purity. Head anointing, in turn, expresses the joy of the inner man who fasts for the sake of God. The Fathers see a link between this anointing and the "oil of gladness" mentioned in Psalms 45 (44):8, with which God anoints His chosen one. The joy of fasting is also derived from the many spiritual benefits that the fasting brings. Anointing with oil had a rich meaning in the biblical and ancient world, taken over by our authors. This is a participation in the mystery of Christ as the Anointed One, High Priest and Head of the Mystical Body. While face washing denotes getting rid of evil, in some writers head anointing symbolizes good deeds and, above all, works of mercy. The association with an athlete getting anointed before the fight implies seeing fasting as a fight. The pleasant scent of oil, in turn, indicates the apostolic nature of Christian mortification, which brings others closer to the faith and urges them to follow suit.